2019
DOI: 10.1007/s40618-019-01088-5
|View full text |Cite
|
Sign up to set email alerts
|

Features and outcome of differentiated thyroid carcinoma associated with Graves’ disease: results of a large, retrospective, multicenter study

Abstract: Background Whether differentiated thyroid cancer (DTC) occurring concomitantly with Graves' disease (GD) is more aggressive and bound to a less favorable outcome is controversial. Objective Aim of this multicenter retrospective study was to compare baseline features and outcome of DTC patients with GD (DTC/GD+) or without GD (DTC/GD−). Patients Enrolled in this study were 579 patients referred to five endocrine units (Cagliari, Pavia, Pisa, Siena, and Varese) between 2005 and 2014: 193 patients had DTC/GD+ ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
3
12
1
Order By: Relevance
“…In only a few studies, US was performed in all GD patients, including non-surgically treated patients as in our study, and these studies reported lower incidences of thyroid cancer. A recent multicenter study performing preoperative US in all GD patients reported that only 38.3% of GD patients with coexisting thyroid cancer underwent thyroidectomy with suspicious FNA results and the ratio of microcarcinoma (<1 cm) was significantly higher in GD patients compared to age, sex, and tumor size-matched non-GD patients (60% vs. 37%) [37]. Our study revealed a similar ratio of microcarcinoma in GD patients, even though thyroid cancer was diagnosed by preoperative US-guided FNA in 95.8% of GD patients.…”
Section: Article In Pressmentioning
confidence: 99%
“…In only a few studies, US was performed in all GD patients, including non-surgically treated patients as in our study, and these studies reported lower incidences of thyroid cancer. A recent multicenter study performing preoperative US in all GD patients reported that only 38.3% of GD patients with coexisting thyroid cancer underwent thyroidectomy with suspicious FNA results and the ratio of microcarcinoma (<1 cm) was significantly higher in GD patients compared to age, sex, and tumor size-matched non-GD patients (60% vs. 37%) [37]. Our study revealed a similar ratio of microcarcinoma in GD patients, even though thyroid cancer was diagnosed by preoperative US-guided FNA in 95.8% of GD patients.…”
Section: Article In Pressmentioning
confidence: 99%
“…Cappelli et al . found a cancer rate of 6.5% in GD patients undergoing thyroidectomy compared to 4.4% of those with solitary toxic nodules ( 90 ), and some studies found that tumors in adult GD patients may behave more aggressively ( 91 , 92 , 93 ). A meta-analysis of 987 GD patients with DTC confirmed the higher prevalence of adverse prognostic features, but there was no difference in persistent disease or mortality ( 94 ).…”
Section: Thyroid Cancer Risk In Pediatric Gd Patientsmentioning
confidence: 99%
“…The presence of nodules increases the chance of finding cancer, a metanalysis revealed that the presence of at least one nodule is associated with a fivefold increase in thyroid cancer risk [ 10 ]. The most common cancer reported in GD is PTC and microcarcinomas are particularly common [ 7 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%